Uso da água, agricultura e florestas: diagnóstico e percepção de atores locais em tempos de mudanças climáticas - Gallo, Mariane de Cássia (2023)
Landscapes, dynamic in nature, are constantly transformed to better adapt to human needs and now need to inspire another movement: how can people place the landscape at the center of their reflections? With the advance of the predatory use of natural resources, we see fundamental elements such as water uffering impacts in its natural cycle and consequently threatening the future supply, mainly of the most vulnerable communities. Climate change, intensified by anthropic action, is a major challenge in many spheres, including water security. Thus contextualized, this work aims to analyze the perception, in a section of the local community, about the changes in the landscape in the watershed of Ribeirão do Meio in Leme/SP. In addition to the identification of physical aspects, evaluated through a bibliographical and cartographic review, it was intended to expand the look to the perception of citizens, with special concern to the view of family farmers. For this purpose, semi-structured interviews were applied and subsequently analyzed quantitatively and qualitatively, using Bardin's categorical content analysis method. The results pointed to a convergence between the collected reports and the data found in the researched bases, such as the census surveys of the Brazilian Institute of Geography and Statistics (IBGE). Impressions about changes in the rainfall regime and increased drought echoed with the trends identified in the 2022 Situation Report, prepared by the Mogi Guaçu River Basin Committee (UGRHI- vi 09). The percentage of native vegetation cover in the study area is lower than the state average of 22.9% (Forestry Inventory of the State of São Paulo, 2020), while a large part of the territory is occupied for the development of different economic activities. In view of the context described, it is understood that the community's point of view is fundamental to be the focus and basis for future planning aimed at maintaining ecosystem services in the basin and elaborated according to the real desires of those who occupy and live in this land.